(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the classification and collection of solid medical waste of some general public hospitals in Vietnam in 2017. Research method: A cross-sectional quantitative study was conducted at 200 departments of 40 general public hospitals. Results: Indicators of containers of solid medical waste made up from 67,5%, to 95,5%; 54% was percentage for achieving all indicators, in which national hospitals accounted for 53,3%, provincial hospitals accounted for 67,3%, district hospitals accounted for 47,8%. In terms of classification of solid medical waste, it accounted for 72% to 97%; achieving all indicators accounted for 53%, in which national hospitals accounted for 46,7%, provincial hospital accounted for 63,3%, district hospitals accounted for 49,6%. Collection of solid medical waste accounted for 68,5% to 93,5%; achieving all indicators accounted for 44%, in which national hospitals were made up 50%, provincial hospitals made up 60%, district hospitals made up 34,8%. Conclusion: Hospitals have not fully complied with regulations of classification and collection of solid medical waste.